Targeting backdoor androgen synthesis through AKR1C3 inhibition: A presurgical hormonal ablative neoadjuvant trial in high‐risk localized prostate cancer. Issue 7 (23rd March 2021) - Graham, Laura S.; True, Lawrence D.; Gulati, Roman; Schade, George R.; Wright, Jonathan; Grivas, Petros; Yezefski, Todd; Nega, Katie; Alexander, Katerina; Hou, Wen‐Min; Yu, Evan Y.; Montgomery, Bruce; et al.
Abstract: Background: Localized prostate cancers (PCs) may resist neoadjuvant androgen receptor (AR)‐targeted therapies as a result of persistent intraprostatic androgens arising through upregulation of steroidogenic enzymes. Therefore, we sought to evaluate clinical effects of neoadjuvant indomethacin (Indo), which inhibits the steroidogenic enzyme AKR1C3, in addition to combinatorial anti‐androgen blockade, in men with high‐risk PC undergoing radical prostatectomy (RP). Methods: This was an open label, single‐site, Phase II neoadjuvant trial in men with high to very‐high‐risk PC, as defined by NCCN criteria. Patients received 12 weeks of apalutamide (Apa), abiraterone acetate plus prednisone (AAP), degarelix, and Indo followed by RP. Primary objective was to determine the pathologic complete response (pCR) rate. Secondary objectives included minimal residual disease (MRD) rate, defined as residual cancer burden (RCB) ≤ 0.25cm 3 (tumor volume multiplied by tumor cellularity) and elucidation of molecular features of resistance. Results: Twenty patients were evaluable for the primary endpoint. Baseline median prostate‐specific antigen (PSA) was 10.1 ng/ml, 4 (20%) patients had Gleason grade group (GG) 4 disease and 16 had GG 5 disease. At RP, 1 (5%) patient had pCR and 6 (30%) had MRD. Therapy was well tolerated. Over a median follow‐up of 23.8 months, 1 of 7 (14%) men with pathologic response and 6 of 13 (46%) men without pathologic response had a PSA relapse. There was no association between prostate hormone levels or HSD3B1 genotype with pathologic response. Conclusions: In men with high‐risk PC, pCR rates remained low even with combinatorial AR‐directed therapy, although rates of MRD were higher. Ongoing follow‐up is needed to validate clinical outcomes of men who achieve MRD.